Dietary Psidium guajava, guava leaf extract protects Oreochromis niloticus, Nile tilapia from Pseudomonas aeruginosa infection and enhances growth - Md. Mer Mosharraf Hossain; Shirin Akter; Bipul Kumar Dey; Tahani Awad Alahmadi; Mohammad Javed Ansari; Nimur Rahman; Suraiya Alam Rojoni; Ummay Rubayea; Suraiya Afrin Bristy; Md. Bayzed Hossain; Md. Mahbub Alam; Bipul Kumar Sen; et al. (Comparative Immunology Reports)
This study investigated the impact of dietary guava leaf extract (GLE) on immunity, resistance to Pseudomonas aeruginosa infection, and growth in Oreochromis niloticus (Nile tilapia). Four groups of fish (28.6 g.fish−1) were fed diets supplemented with ethanolic GLE at 0 (control), 3, 5, or 7 g.fish−1 diet (GLE0diet, GLE3diet, GLE5diet, GLE7diet) at 28 °C. Fish were fed thrice daily at 15 g.kg−0.8.d−1 for 42 days. Innate immune parameters, including mucus-bactericidal activity (MBA), serum-bactericidal activity (SBA), bacterial agglutination activity (BAA), and phagocytic activity (PA), were assessed on days 14, 28, and 42. Weight gain (WG), specific growth rate (SGR), and feed conversion ratio (FCR) were measured on day 42. Post-feeding, fish were injected with P. aeruginosa, and mortality was recorded for 30 days. Results showed that GLE7diet significantly increased MBA, SBA, BAA, and PA by 1.8-, 3.3-, 4.2-, and 3.5-fold, respectively, compared to control. GLE7diet also showed the highest significant reduction in post-challenge mortality (21 %) compared to the control group (83 %). Growth metrics for GLE7diet showed WG of 43.8 g, SGR of 2.21%.d−1, and FCR of 1.19, compared to WG of 37.1 g, SGR of 1.98%.d−1, and FCR of 1.41 in the control group. SGR showed an exponential increase (R² = 0.935) and FCR a decrease (R² = 0.958) with increasing GLE levels. GLE5diet and GLE7diet significantly increased MBA at all-time points compared to control. GLE7diet significantly increased SBA on days 14, 28, and 42 compared to control. GLE7diet significantly enhanced BAA at all-time points. GLE5diet and GLE7diet significantly increased PA at all time points compared to control. GLE7diet led to increased expression of IL-1, IL-6, IFN-α, IFN-β, and TNF-α genes, particularly from 10 to 30 days post-infection. Dietary GLE at 7 g.kg−1 significantly enhanced innate and acquired immune responses, growth performance, and resistance to P. aeruginosa in Nile tilapia. This study recommended incorporating 7 g.kg−1 GLE in Nile tilapia diets to improve disease resistance and growth performance.